2017
DOI: 10.1186/s40814-017-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Potentially effective therapy of heavy menstrual bleeding with an oestradiol-nomegestrol acetate oral contraceptive: a pilot study

Abstract: BackgroundHeavy menstrual bleeding (HMB) exceeding 80 mL per cycle leads to considerable adverse impact on a woman’s iron metabolism, incidence of iron deficiency and anaemia, as well as her functioning in society.The objective of the study is to determine the potential efficacy of a Monophasic oestradiol-17β-nomegestrol acetate (E2/Nomac) combined oral contraceptive pill on measured menstrual blood loss as a pilot study in 12 women with objectively demonstrated HMB (>80 mL per cycle). The pilot study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This may be related to the occurrence of menstrual bleeding during this phase. Despite menstrual losses being smaller in OC cycles than eumenorrheic cycles, 37 lower plasma iron concentrations are still observed during menses. In addition, the present results showed a trend for hepcidin concentrations to be higher at baseline than during the withdrawal phase, which along with menstrual bleeding may reduce the availability of iron in plasma during that phase.…”
Section: Discussionmentioning
confidence: 92%
“…This may be related to the occurrence of menstrual bleeding during this phase. Despite menstrual losses being smaller in OC cycles than eumenorrheic cycles, 37 lower plasma iron concentrations are still observed during menses. In addition, the present results showed a trend for hepcidin concentrations to be higher at baseline than during the withdrawal phase, which along with menstrual bleeding may reduce the availability of iron in plasma during that phase.…”
Section: Discussionmentioning
confidence: 92%
“…Its progesterone activity is higher than that of MPA [28]. The longer half-life and less adverse effects of NOMAC lead to it being successfully used in contraception and in the treatment of many hormone-dependent gynecological disorders, including menstrual disturbances, heavy menstrual bleeding, and premenstrual syndrome [28,29,30]. Preliminarily, we found that NOMAC inhibited the growth of RL95-2 EC cells and the inhibitory effect was stronger than that of MPA [31].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that COCs can modulate these immune cells in many ways. First, COCs could cause a reduction in menstrual bleeding [ 38 , 39 ] and consequently, menstrual reflux into the pelvic cavity. This reduction would then decrease inflammatory reactions and local estrogen production.…”
Section: Discussionmentioning
confidence: 99%